Association between maloclusion and self-perception of oral aesthetics in adolescents - ANA DE LOURDES DE LIRA; Joyce Pires Barros da Cunha; Rebeca Maria Vieira Pereira; Alice Rodrigues Santos; Maria Karen Vasconcelos Fontenele; Ronaldo Carvalho Pinto de Almeida (Universidade Estadual de Campinas, 2020)
Aim: To evaluate the aesthetic self-perception capacity of adolescents from public schools regarding the presence of oral alterations from malocclusions. Methods: Cross-sectional and quantitative study with 374 adolescents between 16 and 18 years old, belonging to public schools in the city of Parnaíba, Piauí. The adolescents were separated by gender (male and female) and examined for malocclusions. The problem identified for each participant was recorded for later comparison of the influence of its presence with aesthetic self-perception. Then, all adolescents, including those who demonstrated normal occlusion during the clinical evaluation, answered a questionnaire containing eight questions about their perception of their own smile and its impact on their interpersonal relationships. Self-perception was also analyzed by comparing the responses of those with normal occlusion with that of malocclusion individuals. Student's t-tests were used to verify if there was a difference between the groups. Results: The most prevalent malocclusions after clinical examination were midline deviations, crowding and diastemas, and the ones that most scored in the adolescents' perception were crowding, misalignment and diastemas. Conclusion: The adolescents were able to perceive the aesthetic alterations resulting from malocclusions, being determinants of dissatisfaction when smiling. They were not ashamed to smile, did not consider that the ideal smile would improve their self-esteem and that misaligned teeth would not interfere with flirting and interpersonal relationships.